Prospects for the North America’ shale hydrocarbons development - T. V. Polyakova (Vestnik MGIMO-Universiteta)
An entire generation of American politicians were concerned about the growing U.S. dependence on imported oil and natural gas. However, in the last few years the situation has changed dramatically: there was started the development of not only the resources of shale gas, but shale oil. As a result in political and economic circles they began to talk about it as the most significant breakthrough in the energy resources development since the oil boom in Texas in the late 1920s. How large are these resources? What problems have to be overcome if the available potential will be realized? How will this problems affect the U.S. energy policy? Concerns about the adequacy of regulation, in particular the environmental issues associated with the non-conventional hydrocarbons production, have led to the internal public debate on the impact of unconventional oil and gas resources mining boom. One thing is clear: significant amounts of additional oil and gas supplies in the U.S. will have far-reaching political consequences for the world. The article presents the different points of view on the prospects for oil and gas production in North America, as well as on the political issues related to it.